The courts as political players - Sara Rosenbaum (BMC, 2019)
Abstract Courts are political animals; as a result, they strive not only to carry out their assigned role in national governance but also to balance that role within the political and social system in which they operate. Sperling and Cohen offer an elegant, in-depth analysis of how these institutional interests have helped shape decision-making by the Israeli Supreme Court in a health policy context. In doing so, the authors tell a universal story, one with enormous resonance in the U.S.